PERSUASIVE POWER IN THE DIGITAL AGE: A STUDY ON GOJEK USERS’ PURCHASE INTENTION IN DEPOK CITY THROUGH COPYWRITING, CONTENT MARKETING, AND BRAND AWARENESS - Bun, Lunie; Hilmiyah, Nurul; Ichwani, Tia (INQUISITIVE : International Journal of Economic, 2025)
This research aims to examine the influence of Copywriting, Content Marketing, and Brand Awareness on Purchase Intention in Gojek products (Case Study of Gojek Users in Depok City). The type of data used is primary data. The sample used came from 100 respondents. The data source used is the respondents’ answers from the questionnaire distributed. The data analysis techniques used are Validity Test, Realibility Test, Classical Assumption Test, Statistical Test, and Hypothesis Test. This research uses the SPSS 25 data processing system. The results of this research partially show that Copywriting, Content Marketing, and Brand Awareness have a positive and significant effect on buying interest in Gojek products in Depok City. The results of this research simultaneously show that Copywriting, Content Marketing, and Brand Awareness have a positive and significant effect on purchasing interest in Gojek products.